Reproducibility of R 2 and quantitative susceptibility mapping (QSM) reconstruction methods in the basal ganglia of healthy subjects - Santin, M. D.; Didier, M.; Valabrègue, R.; Yahia Cherif, L.; García‐Lorenzo, D.; Loureiro de Sousa, P.; Bardinet, E.; Lehéricy, S. (NMR in biomedicine, 2017)
The basal ganglia are key structures for motor, cognitive and behavioral functions. They undergo several changes with aging and disease, such as Parkinson's or Huntington's disease, for example. Iron accumulation in basal ganglia is often related to these diseases, which is conventionally monitored by the transverse relaxation rate ( R 2 *). Quantitative susceptibility mapping (QSM) is a novel contrast mechanism in MRI produced by adding information taken from the phase of the MR signal to its magnitude. It has been shown to be more sensitive to subtle changes in Parkinson's disease . In order to be applied widely to various pathologies, its reproducibility must be evaluated in order to assess intra‐subject variability and to disseminate into clinical and pharmaceutical studies. In this work, we studied the reproducibility and sensitivity of several QSM techniques. Fourteen subjects were scanned four times, and QSM and R 2 * images were reconstructed and registered. An atlas of the basal ganglia was used to automatically define regions of interest. We found that QSM measurements are indeed reproducible in the basal ganglia of healthy subjects and can be widely used as a replacement for R 2 * mapping in iron‐rich regions. This reproducibility study could lead to several lines of research in relaxometry and susceptibility measurements, in vivo iron load evaluation as well as pharmacological assessment and biomarker development. Copyright © 2016 John Wiley & Sons, Ltd.